1989
DOI: 10.1177/026010608900600303
|View full text |Cite
|
Sign up to set email alerts
|

Food Sensitivities and Psychological Disturbance: a Review

Abstract: The literature dealing with the relationship between food sensitivities and psychological disturbance is reviewed. Numerous theorists and researchers believe the problems of persons presenting with adverse reactions to foods are psychological when immunological techniques fail to confirm an allergic basis. However, there is mounting evidence that adverse reactions to foods can most likely be caused by a variety of mechanisms, and that food sensitivities may indeed cause or exacerbate symptoms of a psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A plethora of epidemiological and clinical data suggests higher incidence of anxiety and increased emotional reactivity in individuals suffering from allergies [1521]. In studies of food allergy, specifically, it has been shown that the prevalence of anxiety or depression is higher in adults with food allergy than in nonhealthy controls with lactose intolerance or in healthy controls [22].…”
Section: Neural Activity In Allergymentioning
confidence: 99%
“…A plethora of epidemiological and clinical data suggests higher incidence of anxiety and increased emotional reactivity in individuals suffering from allergies [1521]. In studies of food allergy, specifically, it has been shown that the prevalence of anxiety or depression is higher in adults with food allergy than in nonhealthy controls with lactose intolerance or in healthy controls [22].…”
Section: Neural Activity In Allergymentioning
confidence: 99%